2011
DOI: 10.1088/1742-5468/2011/03/p03027
|View full text |Cite
|
Sign up to set email alerts
|

Air-fluidized balls in a background of smaller beads

Abstract: We report on quasi-two-dimensional granular systems in which either one or two large balls is fluidized by an upflow of air in the presence of a background of several hundred smaller beads. A single large ball is observed to propel ballistically in nearly circular orbits, in direct contrast to the Brownian behavior of a large ball fluidized in the absence of this background. Further, the large ball motion satisfies a Langevin equation with an additional speed-dependent force acting in the direction of motion. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For a vibrated monolayer of steel balls [24], a plateau appears in the MSD at φ ≈ 0.7. It is reported that the caging occurred at φ ≈ 0.7 for fluidized ping-pong balls (ρ = 0.08 g cm −3 ) [13], while for fluidized beads no caging was observed [6]. Fluidized bidispersed steel balls [5] exhibit strong caging at φ = 0.74 but do not show subdiffusion for φ < 0.64.…”
Section: Caging Effectmentioning
confidence: 97%
See 1 more Smart Citation
“…For a vibrated monolayer of steel balls [24], a plateau appears in the MSD at φ ≈ 0.7. It is reported that the caging occurred at φ ≈ 0.7 for fluidized ping-pong balls (ρ = 0.08 g cm −3 ) [13], while for fluidized beads no caging was observed [6]. Fluidized bidispersed steel balls [5] exhibit strong caging at φ = 0.74 but do not show subdiffusion for φ < 0.64.…”
Section: Caging Effectmentioning
confidence: 97%
“…This leads to an analogy to the thermal system despite the dissipative and macroscopic dynamics in the many-particle system. Actually many studies in recent years have found that various macroscopic, strongly dissipative (and thus out-of-equilibrium) systems such as particles agitated by turbulent airflow [3][4][5][6][7][8] or by mechanical vibration [9][10][11], can mimic Brownian behavior to an appreciable degree which has long been considered mainly in the context of energetically closed system. Thus far a variety of studies on macroscopic two-dimensional systems have been conducted [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%